Peningkatan Pembelajaran Keterampilan Berbicara Melalui Media Gambar Seri di Kelas III SDN 17 Batang Anai Kabupaten Padang Pariaman - Surida Surida (Jurnal Konseling dan Pendidikan, 2016)
Usually, students feel reluctant to speak in front of classroom. It is caused by learning Bahasa that only focus on reading and writing skill, but less on speaking skill. This research is aimed to improve speaking skill of elementary students grade III in SDN 17 Batang Anai Kabupaten Padang Pariaman by implementing serial pictures media. This is a class action research that consists of two cycles including four steps: planning, action, observation, and reflection. Data of research were obtained through observation, interview, and test. Obtained data were analyzed quantitatively and qualitatively. Learning output of students is improved in each cycle.In cycle I, the percentage of students’ speaking skill is 53.3%. Meanwhile in cycle II, the percentage of students’ speaking skill is 86%. Hence, it can be concluded that Bahasa learning that use serial pictures media can improve speaking skill of elementary students grade III.